Hurst Exponent Analysis of Resting-State fMRI Signal Complexity across the Adult Lifespan - Dong, Jianxin; Jing, Bin; Ma, Xiangyu; Liu, Han; Mo, Xiao; Li, Haiyun (Frontiers in Neuroscience, 2018)
Exploring functional information among various brain regions across time enables understanding of healthy aging process and holds great promise for age-related brain disease diagnosis. This paper proposed a method to explore fractal complexity of the resting-state functional magnetic resonance imaging (rs-fMRI) signal in the human brain across the adult lifespan using Hurst exponent (HE). We took advantage of the examined rs-fMRI data from 116 adults 19 to 85 years of age (44.3±19.4 years, 49 females) from NKI/Rockland sample. Region-wise and voxel-wise analyses were performed to investigate the effects of age, gender and their interaction on complexity. In region-wise analysis, we found that the healthy aging is accompanied by a loss of complexity in frontal and parietal lobe and increased complexity in insula, limbic and temporal lobe. Meanwhile, differences in HE between genders were found to be significant in parietal lobe (p=0.04, corrected). However, there was no interaction between gender and age. In voxel-wise analysis, the signiﬁcant complexity decrease with aging was found in frontal and parietal lobe, and complexity increase was found in insula, limbic lobe, occipital lobe and temporal lobe with aging. Meanwhile, differences in HE between genders were found to be significant in frontal, parietal and limbic lobe. Furthermore, we found age and sex interaction in right parahippocampal gyrus (p=0.04, corrected). Our findings reveal HE variations of the rs-fMRI signal across the human adult lifespan and show that HE may serve as a new parameter to assess healthy aging process.